One-pot size-controlled growth of graphene-encapsulated germanium nanocrystals - Lee, Jae Hyun; Lee, Eun Kyung; Kang, Seog Gyun; Jung, Su Ho; Son, Seok Kyun; Nam, Woo Hyun; Kim, Tae Hoon; Choi, Byong Lyong; Whang, Dongmok (Applied Surface Science, 2018)
To realize graphene-encapsulated semiconductor nanocrystals (NCs), an additional graphene coating process, which causes shape destruction and chemical contamination, has so far been inevitable. We report herein one-pot growth of uniform graphene-germanium core–shell nanocrystals (Ge@G NCs) in gram scale by the addition of methane as a carbon source during the thermal pyrolysis of germane. The methane plays a critical role in the growth of the graphene shell, as well as in the determination of the nucleation density and diameter of the NCs, similar to a surfactant in the liquid-phase growth of monodisperse NCs. By adjusting the gas ratio of precursors, a mixture of germane and methane, we can control the size of the Ge@G NCs in the range of ∼5–180 nm. The Ge@G NCs were characterized by various microscopic and spectroscopic tools, which indicated that the Ge core is single crystalline, and is completely covered by the graphene shell. We further investigated the merits of the graphene shell, which can enhance the electrical conductivity of nanocrystalline materials.
Keywords: Chemical vapor depositions (CVD); Electrical conductivity; Germanium nanocrystals; Nucleation densities; Semiconductor nanocrystals; Single-crystalline; Size-controlled growth; Thermoelectric; Chemical vapor deposition (CVD); Core–shell; Germanium; Graphene; Nanocrystal; Thermoelectric